Yield Potential, Economics and Nutrient Uptake of Rabi Sweet Corn (Zea mays saccharata) as Influenced by Varying Plant Densities and Nitrogen Rates - N. R, Sandya; Subbaiah, G.; Rao, CH. Pulla (International Journal of Bio-resource and Stress Management, 2023)
A field experiment was conducted during rabi, 2013-14 on clay loam soil of Agriculture College Farm, Bapatla, Andhra Pradesh, India to study the influence of plant densities and nitrogen rates on yield, economics and nutrient uptake of sweet corn (Zea mays saccharata). The treatments consisted of combination of three planting densities (P1: 1,11,111 plants ha-1, P2: 83,333 plants ha-1 and P3: 66,666 plants ha-1) and four nitrogen levels (N1: 120 kg N ha-1, N2: 170 kg N ha-1, N3: 220 kg N ha-1 and N4: 270 kg N ha-1). Significantly higher value of yield attributes were noticed with planting density of 66,666 plants ha-1 and nitrogen level of 270 kg ha-1. Significant green cob and green fodder yield of sweet corn were recorded at planting density of 83,333 plants ha-1 and 1,11,111 plants ha-1 respectively with the application of 270 kg N ha-1. The maximum nutrient uptake by sweet corn crop and stover was noticed with planting density of 83,333 plants ha-1and 1,11,111 plants ha-1 respectively with the application of 270 kg N ha-1. The highest net returns and B:C ratio were recorded with application of 270 kg N ha-1 at planting density of 83,333 plants ha-1 over all other treatment combinations. Hence, plant density of 83,333 plants ha-1 with nitrogen level of 270 kg N ha-1 should be adopted to obtain the maximum nutrient uptake, green cob yield and net profit from sweet corn in Krishna Agro-climatic zone of Andhra Pradesh.